2018
DOI: 10.3390/antiox7110151
|View full text |Cite
|
Sign up to set email alerts
|

Hmox1 Upregulation Is a Mutual Marker in Human Tumor Cells Exposed to Physical Plasma-Derived Oxidants

Abstract: Increasing numbers of cancer deaths worldwide demand for new treatment avenues. Cold physical plasma is a partially ionized gas expelling a variety of reactive oxygen and nitrogen species, which can be harnesses therapeutically. Plasmas and plasma-treated liquids have antitumor properties in vitro and in vivo. Yet, global response signatures to plasma treatment have not yet been identified. To this end, we screened eight human cancer cell lines to investigate effects of low-dose, tumor-static plasma-treated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 74 publications
5
20
0
Order By: Relevance
“…Several studies by others and us have observed plasma-induced tumor cell death before [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98]. Kumar and colleagues observed in several pancreatic cancer cell lines an increase in apoptosis concomitant with downregulation of MAPK7, BCL2, and CHK1 [99].…”
Section: Discussionmentioning
confidence: 94%
“…Several studies by others and us have observed plasma-induced tumor cell death before [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98]. Kumar and colleagues observed in several pancreatic cancer cell lines an increase in apoptosis concomitant with downregulation of MAPK7, BCL2, and CHK1 [99].…”
Section: Discussionmentioning
confidence: 94%
“…However, while the physical modalities mentioned generate ROS in the interior of cells, gas plasma treatment adds ROS from the outside with mechanisms and redox‐chemical reaction pathways only starting to be understood as of now. [ 78–80 ] Due to the mechanism of action, gas plasma produced ROS may only act in a localized manner but not systemically.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmas are multi-component systems generating UV radiation, visible light, electromagnetic fields, thermal radiation, electrons and ions, and reactive oxygen species (ROS) and reactive nitrogen species (RNS) [2]. The latter play a crucial role in mediating the plasma effects in cells [3][4][5] by mediating oxidative modifications [6][7][8] to induce signaling pathways [9][10][11]. First discovered as a new tool for disinfection and wound healing [12][13][14], plasma also demonstrates cytotoxicity towards cancer cells [15][16][17].…”
Section: Introductionmentioning
confidence: 99%